Sedition in Wartime Ontario: The Trials and Imprisonment of Isaac Bainbridge, 1917-1918 - Milligan, Ian (Ontario History, 2008)
This article examines the trials and imprisonment of Isaac Bainbridge, publisher of the Social Democratic Party of Canada’s newspaper Canadian Forward, for seditious libel between 1917 and 1919. Charged and convicted for his opposition to militarism, capitalism and conscription, Bainbridge’s encounter with the legal system illustrates the degree to which the courts acted as both a coercive force and as a space for resistance. While the selective nature of seditious libel became apparent during the trial, conflict between the judiciary and the government allowed Bainbridge to obtain his release from prison on a legal technicality.